The effect of balanced nutrition on developing the muscular capacity of bodybuilding athletes - Bouchher , Houari (sports creativity, 2025)
The study aimed to find out the impact of balanced nutrition according to a proposed dietary program in the development of the muscular capacity of bodybuilders. Through the theoretical study of the subject, the researcher found that the development of the muscular capacity of athletes requires measuring the muscular ability of the men, arms and abdomen. In this study, the researcher used the one-group-designed experimental method and relied on a sample of 4 athletes practicing bodybuilding. The results have also found statistically significant differences between tribal and dimensional measurements in each of the three indicators (the muscular capacity of the men, arms and abdomen), which confirms the positive effect of balanced nutrition in Developing the muscular capacity of bodybuilders